shRNA干扰蛋白激酶D-2基因提高Tca8113对化疗药物的敏感性研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: To explore the effect of silencing protein kinase D (PKD)-2 on Tca8113 cell proliferation, programmed cell death, and chemosensitivity. METHODS: The stable cell lines of pkd-2 gene silencing and empty vector plasmid group were established. The proliferation and 50% inhibitory concentration (IC(50)) of shRNA-mediated Tca8113 chemotherapy drugs were detected through methyl thiazolyl tetrazolium assay (MTT). The programmed cell death rate and sensitivity to Tca8113 chemotherapy drugs before or after pkd-2 gene silencing were measured through flow cytometry. P-glycoprotein (P-gp) expression of pkd-2 silencing cells was identified by immunohistochemical methods. RESULTS: Stable cell lines of pkd-2 gene silencing were established. Compared with parental cells, the proliferation of shRNA-mediated Tca8113 was not significantly different, but its IC(50) was lower. Meanwhile, cell programmed death rate and sensitivity to chemotherapeutic drugs of shRNA-mediated Tca8113 significantly increased. Compared with wild group Tca8113, a significant decrease in P-gp expression was induced by chemotherapy drugs with shRNA-pkd-2 gene silencing. CONCLUSION: The pkd-2 gene of shRNA interference silencing Tca8113 promotes programmed cell death of Tca8113, reduces the IC(50) of the chemotherapy drugs, and significantly improves the sensitivity of Tca8113 to chemotherapeutic drugs while reducing the expression of P-gp.